1999
DOI: 10.1007/s004360050630
|View full text |Cite
|
Sign up to set email alerts
|

Secondary amoebic eye infections in mice due to Acanthamoeba sp.

Abstract: The aim of the present study was to determine the occurrence of eye infections accompanying the infection of the central nervous system and to demonstrate the possible tissue affinity of different strains of amoebae in subsequent infections. The results obtained demonstrate a clear correlation between the occurrence of eye infection and the degree of virulence of the strains. Amoebae isolated from eyeballs and other organs of dead mice did not exhibit any specificity in relation to the organs in subsequent inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…During human infection, strains of Acanthamoeba affect several organs in addition to the brain, including the skin, liver, lungs, kidneys, heart, diaphragm, eyes, adrenal glands, pancreas, prostate, lymph nodes and bone marrow (Mazur & Jóźwiak 1993, Khan 2010, Young et al 2010. Mortazavi et al (2009) studied Acanthamoeba infections in locusts and observed that the insects developed disseminated infections in the haemolymph, fat body, muscle and brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…During human infection, strains of Acanthamoeba affect several organs in addition to the brain, including the skin, liver, lungs, kidneys, heart, diaphragm, eyes, adrenal glands, pancreas, prostate, lymph nodes and bone marrow (Mazur & Jóźwiak 1993, Khan 2010, Young et al 2010. Mortazavi et al (2009) studied Acanthamoeba infections in locusts and observed that the insects developed disseminated infections in the haemolymph, fat body, muscle and brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, apart from differences in predisposition of patients, one can assume that amoeba strains vary in pathogenicity. Mazur et al demonstrated in an animal model a clear correlation between the occurrence of eye infections and the degree of virulence of the strains after installation into the brain (19), which suggests that pathogenicity is not so much dependent on environmental conditions but rather represents a distinct characteristic of certain strains. Nevertheless the initial infective dose is certainly of considerable importance.…”
Section: Discussionmentioning
confidence: 99%
“…GAE symptoms common to other of CNS diseases can cause misdiagnosis; magnetic resonance imaging and computed tomography are helpful for this reason. GAE develops in persons with HIV/AIDS and those who are immunocompromised or undergoing immunosuppressive therapy [ 8 , 9 , 10 ]. The amebae enter the human body through the nose and into to bloodstream, crossing blood–brain barrier and invade the CNS; infections via skin lesions or the respiratory tract are also likely.…”
Section: Granulomatous Amoebic Encephalitis (Gae)mentioning
confidence: 99%
“…The amebae enter the human body through the nose and into to bloodstream, crossing blood–brain barrier and invade the CNS; infections via skin lesions or the respiratory tract are also likely. Complex therapy (ketoconazole, azithromycin, and pentamidine isethionate) is less effective due to the resistance of Acanthamoeba to chemicals and the inability of drugs to cross the blood–brain barrier [ 3 , 8 , 10 ]. Despite some success in treatment efforts, the prognosis for GAE is still poor.…”
Section: Granulomatous Amoebic Encephalitis (Gae)mentioning
confidence: 99%
See 1 more Smart Citation